The Camelot betrayal - White, Kiersten (White, Kiersten. Camelot rising trilogy, 2020)
When a rescue goes awry and results in the death of something precious, the devastated Guinevere, impersonated by a changeling witch, returns to Camelot to find the greatest threat yet--the real Guinevere's younger sister.